2017
DOI: 10.1080/14397595.2017.1370766
|View full text |Cite
|
Sign up to set email alerts
|

Changes in serum interleukin-6 levels as possible predictor of efficacy of tocilizumab treatment in rheumatoid arthritis

Abstract: Serum IL-6 levels from 12 to 24 weeks after TCZ initiation better reflect the efficacy of TCZ at 52 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 19 publications
1
6
0
4
Order By: Relevance
“…The reduced effects of Tocilizumab in hyperglycemic patients may due to the higher plasma IL-6 levels. Previous study evidenced that tocilizumab efficacy was inversely proportional to the baseline IL-6 levels in patients with rheumatoid arthritis (5). Accordingly, our data evidence that hyperglycemic patients had IL-6 levels at admission 5-fold higher as compared to the normoglycemic patients.…”
supporting
confidence: 66%
“…The reduced effects of Tocilizumab in hyperglycemic patients may due to the higher plasma IL-6 levels. Previous study evidenced that tocilizumab efficacy was inversely proportional to the baseline IL-6 levels in patients with rheumatoid arthritis (5). Accordingly, our data evidence that hyperglycemic patients had IL-6 levels at admission 5-fold higher as compared to the normoglycemic patients.…”
supporting
confidence: 66%
“…In rheumatoid arthritis, IL-6 <30 pg/mL after 12 weeks predicted remission after 52 weeks 4 5. In contrast, others reported a link between lower serum IL-6 at TCZ stop and subsequent GCA flares 3.…”
mentioning
confidence: 97%
“…In this setting, TCZ through its targeting of the IL-6 pathways is a blocker of the IL-6 signal transduction pathway and can be used in patients with severe Covid-19 [8]. Notably, based on a previous study conducted in patients with rheumatoid arthritis, TCZ efficacy was shown to be inversely proportional to baseline IL-6 levels [9]. Moreover, in Covid-19 patients, TCZ treatment led to a significant decline in inflammatory markers, with radiological improvement and reduced ventilator support requirements [10].…”
mentioning
confidence: 99%